PENGARUH VIRAL MARKETING TERHADAP KEPERCAYAAN PELANGGAN DAN KEPUTUSAN PEMBELIAN SATE TAICHAN GORENG MELALUI SOCIAL MEDIA INSTAGRAM DI KOTA BANDUNG - Yuritri Suciati; Nadya Novandriani Karina Moeliono (Departemen Manajemen, 2021)
The study aims to determine (1) the influence of viral marketing on customer trust; (2) ) the influence of viral marketing on purchasing decisions; (3) ) the influence of customer trust on purchasing decisions. This type of research is quantitative and uses descriptive analysismethod. The data analysis technique used is path analysis. The sample used in this study amounted to 100 respondents who knew the social media instagram Sate TaichanGoreng, at least 15 years old, and once bought and consumed Taichan Goreng Satay by using purposive sampling. The data collection method used in this study was a questionnaires. The conclusion of this study is that viral marketing has a direct effect on customer trust by 0.412, viral marketing variables directly influence the purchase decision of 0.401 and variable customer confidence directly affects the purchase decision of 0.396. These results can be interpreted that viral marketing variables significantly influence customer confidence and purchasing decisions Sate Taichan Goreng in the city of Bandung.